The Application of Greimas' Narrative in the Story of the Prophet Yunus: A Structural Semiotic Study of the Quranic Narrative - Wahyu Muhammad Abdul Wahid; Muliadi; Wildan Taufiq (Tilawah: Journal of Al-Qur'an Studies, 2025)
This article examines the story of Prophet Yunus in the Qur'an using A. J. Greimas' structural narrative theory, especially the actant model and narrative functional scheme. This study aims to explore the narrative structure of the story within the framework of structural semiotics in order to show the pattern of meaning transformation and character dynamics in the prophetic journey of Prophet Yunus. The methodology used is a qualitative-descriptive approach with an analysis of related Qur'anic texts, especially in Surah As-Saffat [37]:139–148, Q.S. Al-Anbiya’ [21] : 87-88, Yunus [10]:98, and Al-Qalam [68]:48–50. The results of the analysis show that the narrative structure of the story of Yunus represents six actant positions and three main functional stages that form spiritual and narrative transformation. This study contributes to strengthening the structural approach in the study of narrative interpretation and opens up interdisciplinary space between Qur'anic studies and modern narrative theory.